Pengembangan Jiwa Wawasan Kebangsaan Yang Dipengaruhi Oleh Kemajuan Teknologi AI - Devi Aryani Saputri; Patria Lumban Tobing; Revany Yuliani; Wahjoe Pangestoeti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Artificial intelligence is one of the most talked about technologies today. The advanced technology that allows computers to mimic human behaviour is what defines artificial intelligence. Advanced technology that allows computers to mimic human behaviour is at the core of artificial intelligence. The utilisation of this technology is widespread in all industries around the world. The purpose of this research is to find out how influential the advancement of AI Technology is on the insight of the archipelago. The method used is a qualitative method that emphasises qualitative information data. Qualitative research method is a research method that focuses on understanding a social phenomenon that occurs in society. The result of this discussion is that the development of the times has made technological advances increasingly sophisticated. Technology can facilitate the quick and easy acquisition of information about history, culture, values, and the latest national developments. Technology understands the diversity and uniqueness of each country, so it is expected to give birth to a spirit of solidarity to achieve common progress.